2005
DOI: 10.1112/s0024609304003716
|View full text |Cite
|
Sign up to set email alerts
|

Gaps Between the Zeros of Epstein's Zeta-Functions on the Critical Line

Abstract: Abstract. It is proved that Epstein's zeta-function ζ Q (s) related to a positive definite integral binary quadratic form has a zero 1 2 + iγ with T ≤ γ ≤ T + T 5/11+ε for sufficiently large positive numbers T . This improves a classical result of H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…(A. 15) Next, taking the argument of both sides of (A.11), we get For c not too large, the formula (A.21) can be used to compute f (c) numerically to a decent precision. We have implemented this in [27, numdensity.mpl].…”
Section: ])mentioning
confidence: 99%
See 1 more Smart Citation
“…(A. 15) Next, taking the argument of both sides of (A.11), we get For c not too large, the formula (A.21) can be used to compute f (c) numerically to a decent precision. We have implemented this in [27, numdensity.mpl].…”
Section: ])mentioning
confidence: 99%
“…225-227]) that a positive proportion of the zeros do lie on the critical line. For related results, see also [15] and [19].…”
Section: Introductionmentioning
confidence: 99%
“…Then for any fixed ε > 0 and T ≥ T (ε, Q), there is a zero 1/2 + iγ of the corresponding Epstein zeta-function ζ Q (s) with | γ − T |≤ T 3/7+ε . (1.2) In this paper we indicate those steps in [4] which enabled us to improve the result of Jutila and Srinivas mentioned earlier. Therefore, for technical details the readers are urged to refer to [4] and [3].…”
Section: Introductionmentioning
confidence: 66%
“…Sankaranarayanan in 1995 [9] showed that the same result holds true for intervals of the type [T, T + cT 1/2 log T ]. In 2005, Jutila and Srinivas [4] proved that the same is true for intervals of the type [T, T + cT 5/11+ε ], thus surpassing the classical barrier of 1/2 in exponent of T . In this note we improve this result further.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation